Crashworthiness optimization of circular tubes with functionally-graded thickness. Issue 5 (4th July 2016) - Baykasoglu, Adil; Baykasoglu, Cengiz
Abstract : Purpose: – The purpose of this paper is to develop a new multi-objective optimization procedure for crashworthiness optimization of thin-walled structures especially circular tubes with functionally graded thickness. Design/methodology/approach: – The proposed optimization approach is based on finite element analyses for construction of sample design space and verification; gene-expression programming (GEP) for generating algebraic equations (meta-models) to compute objective functions values (peak crash force and specific energy absorption) for design parameters; multi-objective genetic algorithms for generating design parameters alternatives and determining optimal combination of them. The authors have also utilized linear and non-linear least square regression meta-models as a benchmark for GEP. Findings: – It is shown that the proposed approach is able to generate Pareto optimal designs which are in a very good agreement with the actual results. Originality/value: – The paper presents the application of a genetic programming-based method, namely, GEP first time in the literature. The proposed approach can be used to all kinds of related crashworthiness problems.